Influence of pH on the Properties of SnO2 Nanoparticles Synthesized by Sol-Gel Process - Sudha Periathai1, R.; Jeyakumaran2, N.; Prithivikumaran2, N. (Asian Journal of Chemistry, 2013)
SnO2 nanoparticles with different pH values ranging from 6-10 were synthesized using sol-gel process. The influence of pH on the structural and optical properties of SnO2 nanoparticles were studied using X-ray diffraction, scanning electron microscopy, energy dispersive X-ray, Fourier transform infrared spectroscopy, UV-VIS and photoluminescence spectroscopy studies. X-Ray diffraction study revealed the formation of nano-metre scale SnO2 particles with tetragonal rutile structure in the range of 3-5 nm. The particle size was found to be small for the pH value 8.3. FTIR study indicates the structural confirmation of SnO2 nanoparticles. UV and photoluminescence studies also support our result. SEM study shows plate like morphology. Energy dispersive X-ray analysis confirms the elemental composition of SnO2 nanoparticles. It was concluded that tin oxide nanoparticle prepared at pH value around 8 can be used for various potential applications.